Algorithm for the diagnosis and treatment of primary placental dysfunction in pregnant women of risk groups - O.V. Kravchenko (Publishing House TRILIST, 2021)
Research objective: to evaluate the effectiveness of diagnosis and complex therapy of placental dysfunction (PD) in early stages of gestation. Materials and methods. We examined 110 pregnant women with risk for the primary PD. Exclusion criteria were multiple pregnancies, anomalies of fetal development and internal genital organs of the mother, pregnancy resulting from assisted reproductive technologies. The diagnosis of PD was established in 56 women (group I) based on the assessing the state of extraembryonic structures and blood flow in the spiral and uterine arteries at 12-13 weeks of gestation. The rest of the patients (54 women) entered the control group without PD (group II). Results. All pregnant women with verified PD at 12-13 weeks were prescribed complex drug treatment, which included micronized progesterone, venotonic Normoven, Magnicum, and Artihol. As a result of treatment, already at 22-24 weeks of gestation, the average value of blood flow (resistance index) in the uterine and spiral arteries did not differ significantly in the groups. There was no significant difference in fetometry and placentometry indices at 35-36 weeks of gestation. Complications of the gestational period in patients in the study groups were also almost the same. Conclusions. History of hormonal disorders and miscarriage, clinical signs of miscarriage in early gestation, abnormal embryo placement, extragenital pathology, and genital tract infections are risk factors for PD. Determination of the state of extraembryonic structures at 7-8 weeks of pregnancy (ovum volume, blood flow in the corpus luteum) and at 12-13 weeks (chorion volume, vascularization index, blood flow in the spiral and uterine arteries) can serve as a verification criterion for the PD development. Complex drug therapy, which began from the early stages of gestation (micronized progesterone, Normoven, Magnicum, Artihol) has established itself as an effective method of treating primary PD in pregnant of risk groups.